1994
DOI: 10.3171/jns.1994.80.6.1074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of irradiation on expression of HLA class I antigens in human brain tumors in culture

Abstract: The immunosuppressive effects of irradiation are well known; however, under certain circumstances irradiation also augments the local immune response by as yet undefined mechanisms. Because of the importance of HLA class I antigen in immune regulation and the fact that killing of tumor cells by cytotoxic T cells is HLA antigen-restricted, the authors studied HLA class I antigen expression in eight glioblastomas multiforme, four meningiomas, and four medulloblastomas. Twenty fragments of each tumor specimen wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 15 publications
1
45
1
Order By: Relevance
“…Radiation is known to kill cancer cells via its direct cytotoxic effect and via the induction of radiation-induced immune response [1,14,15]. Similarly, in a previous study, we found that combined hMUC1 vaccination and hNIS radioiodine gene therapy had a good therapeutic effect in a murine cancer model [3].…”
Section: Discussionsupporting
confidence: 73%
“…Radiation is known to kill cancer cells via its direct cytotoxic effect and via the induction of radiation-induced immune response [1,14,15]. Similarly, in a previous study, we found that combined hMUC1 vaccination and hNIS radioiodine gene therapy had a good therapeutic effect in a murine cancer model [3].…”
Section: Discussionsupporting
confidence: 73%
“…Consequently, enhancing HLA1 expression could restore immune visibility in tumour cells. This has been shown possible by irradiation (Klein et al, 1994), hence we next assessed the effects of chemotherapy on HLA1 expression on tumours. Results showed that treatment with BIC25 concentrations of GEM could increase the expression of HLA1 in tumour cells; some of which exhibited low basal levels.…”
Section: Discussionmentioning
confidence: 99%
“…*, P < 0.001. and 95%, respectively; Supplementary Fig. S1A) 5 at 32 days postchallenge. Bioluminescence imaging ( Fig.…”
Section: In Vitro Clonogenic Assaymentioning
confidence: 99%